Efficacy and Prognostic Factors of Sunitinib as First-Line Therapy for Patients With Metastatic Renal Cell Carcinoma in an Arab Population - Badran, Ahmed (JCO Glob Oncol, 2020)
PURPOSE: Antiangiogenic tyrosine kinase inhibitors have been the mainstay first-line therapy for metastatic renal cell carcinoma (mRCC). We reviewed the efficacy of first-line therapy with sunitinib in patients with mRCC in an Arab population. METHODS: Medical records of patients with mRCC treated at a tertiary care center in Saudi Arabia, during the period from 2007 to 2016, were reviewed. Demographic data, treatment received, response, and prognostic factors were analyzed. RESULTS: Fifty-five patients who received sunitinib were identified. The median age was 60 years (range, 18 to 78 years), and 42 of the 55 patients were men (76.3%). International Metastatic RCC Diagnostic Consortium prognostic scores for favorable/intermediate/poor were 14.5%/43.6%/38.2%, respectively. The median performance status was 1, and the median Charlson comorbidity index score was 9. Thirty-seven patients (67.2%) had cytoreductive nephrectomy. Thirty-seven patients (67.2%) had clear cell histology. Twenty-two patients (40%) underwent dose reduction. Twenty-seven patients (49%) received second-line therapy, and seven patients (12.7%) received third-line therapy. Response rates were complete response in one patient (1.8%), partial response in 17 (30.9%), stable disease in 10 (18.1), and disease progression in 20 (36.3%). Progression-free survival (PFS) and overall survival (OS) were 6.0 and 24.7 months, respectively. Univariate analysis showed statistically improved PFS for dose reduction (P = .015) and the development of hypothyroidism (P = .03). It also showed statistically improved OS for dose reduction (P = .035), hypothyroidism (P = .0002), and cytoreductive nephrectomy (P = .0052). Multivariate analysis showed statistically improved PFS for dose reduction (P = .01) and OS for development of hypothyroidism (P = .007). CONCLUSION: Our data for sunitinib in mRCC show significantly lower PFS than expected. The absence of prognostic value of the International Metastatic RCC Diagnostic Consortium scoring system and pathologic subtype warrant further investigation and possible inclusion of genetic scoring in this ethnic group of patients.